2007
DOI: 10.1007/s10526-006-9067-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential for lab rearing of Apanteles taragamae, the larval endoparasitoid of coconut pest Opisina arenosella, on the rice moth Corcyra cephalonica

Abstract: A lab rearing technique was standardised for Apanteles taragamae Viereck (Hymenoptera: Braconidae), the early larval parasitoid of the coconut leafeating caterpillar, Opisina arenosella Walker on the alternate host Corcyra cephalonica Stainton (Lepidoptera: Pyralidae). The parasitoid took 23.3 ± 3.2 days to complete the egg to adult period. Adult longevity for males and females was 15.3 ± 4.6 and 13.8 ± 4.6 days respectively. Fecundity was 14.8 ± 4.3 eggs per female. The percentage parasitism was 60.6 ± 5.7 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…However, some reports about this wasp species indicated that it was gregarious and that it parasitized five other Pyraloidea species in India (Peter and David 1990;Mohan and Sathiamma 2007). For that reason, we believe that the latter wasp species is likely to be different from the one we have received from Taiwan, which is strictly solitary (Huang et al 2003).…”
Section: Introductionmentioning
confidence: 74%
“…However, some reports about this wasp species indicated that it was gregarious and that it parasitized five other Pyraloidea species in India (Peter and David 1990;Mohan and Sathiamma 2007). For that reason, we believe that the latter wasp species is likely to be different from the one we have received from Taiwan, which is strictly solitary (Huang et al 2003).…”
Section: Introductionmentioning
confidence: 74%
“…This study showed that parasitism rate of A. taragamae was 96% (Table 1). Previous study by Mohan and Sathiamma (2007) showed that parasitism of A. taragamae on C. cephalonica and Opisina arenosella was 60.6% and 64.6% respectively. Peter and David (1990) in their study reported that the parasitism of A. taragamae on D. indica depend on the type of D. indica host plants and their larval age.…”
Section: Fecundity Longevity and Parasitism Of A Taragamae In D Imentioning
confidence: 90%
“…Previous research on A. taragamae related with the hosts range (Dannon et al, 2012), biology in Maruca vitrata (Lepidoptera: Pyralidae) (Dannon et al, 2011) and D. indica (Lepidoptera: Pyralidae) as well (Peter & David, 1992), the effect of volatile compound on the adult behavior (Dannon et al, 2010b), functional responses and life cycle parameters (Dannon et al, 2010a), mass rearing (Mohan & Sathiamma, 2007), hyperparasitoid (Peter & David, 1991), and the relationship of body length to fecundity (Nurkomar, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Host specificity has often been reported for Apanteles species (NgiSong et al 1999). However, some reports about A. taragamae indicated that it parasitized five other Pyraloidea species in India (Peter and David 1992;Mohan and Sathiamma 2007). Of these reported hosts, only one, i.e.…”
Section: Physiological Host Rangementioning
confidence: 99%
“…This parasitoid wasp has been reported to parasitize only M. vitrata in Taiwan, from where it has been exported to Benin (Huang et al 2003). However, some reports about the same species in India indicated that it parasitized five other Pyraloidea species (Peter and David 1992;Mohan and Sathiamma 2007). Of these species, only Corcyra cephalonica Stainton (Lepidoptera: Pyralidae) occurs in Benin.…”
Section: Introductionmentioning
confidence: 99%